Una checklist per la gestione dei costi nel trattamento dell’HIV - Sazonov, Vasilisa; Urleb, Uros; Wertheimer, Albert L. (Farmeconomia. Health Economics and Therapeutic Pathways, 2000)
The human immunodeficiency virus (HIV) infection is currently one of the major health problems in the world. Since the first occurrence of the infection 17 years ago until today, many people have died of its devastating consequences and an enormous amount of health-related funds have been spent on the problem. The pandemic is still growing in some areas, and its negative impact on society is in-creasing. This is the main reason why scientists are trying to find the best way to reduce costs and still keep the same level of management or, in some ways, even improve it (e.g., new combination of drugs in one pill—fewer pills to be taken per day). Since HIV infection has been. a fatal, severe, and widespread disease, a so-called global problem, very early in the course of the pandemic the idea of economic evaluation was raised. Published studies mostly presented the antiretroviral drugs in the frames of pharmacoeconomic models or costs of HIV/AIDS according to development of the disease through longer time periods. The cost sections that have to be considered in any pharmacoeconomic study of HIV management are briefly presented. Often the presented costs are confusing and could be misleading. Direct, indirect, and intangible costs are described.